2019
DOI: 10.3390/cancers11071010
|View full text |Cite
|
Sign up to set email alerts
|

Lung-Seeking Metastases

Abstract: Metastases from different cancer types most often affect the lung parenchyma. Moreover, the lungs are among the most frequent sites of growth of metastatic masses of uncertain/unknown lineage of origin. Thus, with regards to pulmonary neoplastic parenchymal nodules, the critical issue is to determine if they are IN the lung or OF the lung. In this review, we highlight the clinical, instrumental and molecular features which characterize lung metastases, mainly focusing on recently advancing and emerging concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 118 publications
3
52
0
1
Order By: Relevance
“…It has been reported that the lung is the second most common site of metastatic focus for almost 25-54% of malignancies developing elsewhere in the body [7] with colorectal, head and neck, and urological tumors having the highest frequencies [8]. Throughout medical history, the emergence of pulmonary metastasectomy has been described as incidental and fortuitous dating back to 1927, when Tudor Edwards described a sublobar resection of a metastatic lower limb sarcoma [4], followed by the rst cohort of 25 patients at Memorial Hospital undergoing pulmonary metastasectomy with either a solitary lung lesion or multiple metastases but con ned to one lung with an unfortunate 10 out of 25 patients surviving more than ve years [5].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the lung is the second most common site of metastatic focus for almost 25-54% of malignancies developing elsewhere in the body [7] with colorectal, head and neck, and urological tumors having the highest frequencies [8]. Throughout medical history, the emergence of pulmonary metastasectomy has been described as incidental and fortuitous dating back to 1927, when Tudor Edwards described a sublobar resection of a metastatic lower limb sarcoma [4], followed by the rst cohort of 25 patients at Memorial Hospital undergoing pulmonary metastasectomy with either a solitary lung lesion or multiple metastases but con ned to one lung with an unfortunate 10 out of 25 patients surviving more than ve years [5].…”
Section: Discussionmentioning
confidence: 99%
“…Inhaled cytotoxic chemotherapy is an approach that is promising for treating localized pulmonary tumors. Pulmonary tumors are usually detected by imaging techniques such as chest radiography, chest computed-tomography after infusion with contrast material and/or positron emission tomography using radiolabelled fluorodeoxyglucose 18 F-FDG [1][2][3][4]. Diagnosis requires mostly biopsy for histological evaluation including immunohistochemistry [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary tumors are usually detected by imaging techniques such as chest radiography, chest computed-tomography after infusion with contrast material and/or positron emission tomography using radiolabelled fluorodeoxyglucose 18 F-FDG [1][2][3][4]. Diagnosis requires mostly biopsy for histological evaluation including immunohistochemistry [1,3,4]. Biopsy is currently made using fiber-optic bronchoscopy for centrally located lesions and mediastinal lymph nodes, percutaneous computed-tomography guided biopsy for peripheral lung nodules, or after surgical resection [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastasis is the predominant cause of cancer-related mortality, responsible for approximately 90% of all cancer deaths (1). It is a multistep process wherein cancer cells at the site of origin spread to secondary tissues and organs; the lungs are a common site of metastasis in a wide range of cancers (2).…”
Section: Introductionmentioning
confidence: 99%